Random fixed point theorems for asymptotic 1-set contraction operators - P. Vijayaraju (International Journal of Mathematics and Mathematical Sciences)
Random fixed point theorems for condensing, 1-set contraction selfless are known. But no random fixed point theorem for more general asymptotic 1-set contraction selfmaps is yet available. The purpose of this paper is to prove random fixed point theorems for such maps.